Role of the Gut Microbiota in Regulating Non-alcoholic Fatty Liver Disease in Children and Adolescents - Tokuhara, Daisuke (Frontiers in Nutrition, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease in children and adolescents. Although obesity is the leading cause of NAFLD, the etiologies of NAFLD are multifactorial (e.g., high-fat diet, a lack of exercise, gender, maternal obesity, the antibiotic use), and each of these factors leads to dysbiosis of the gut microbiota community. The gut microbiota is a key player in the development and regulation of the gut mucosal immune system as well as the regulation of both NAFLD and obesity. Dysbiosis of the gut microbiota promotes the development of NAFLD via alteration of gut-liver homeostasis, including disruption of the gut barrier, portal transport of bacterial endotoxin (lipopolysaccharide) to the liver, altered bile acid profiles, and decreased concentrations of short-chain fatty acids. In terms of prevention and treatment, conventional approaches (e.g., dietary and exercise interventions) against obesity and NAFLD have been confirmed to recover the dysbiosis and dysbiosis-mediated altered metabolism. In addition, increased understanding of the importance of gut microbiota-mediated homeostasis in the prevention of NAFLD suggests the potential effectiveness of gut microbiota-targeted preventive and therapeutic strategies (e.g., probiotics and fecal transplantation) against NAFLD in children and adolescents. This review comprehensively summarizes our current knowledge of the gut microbiota, focusing on its interaction with NAFLD and its potential therapeutic role in obese children and adolescents with this disorder.